Pelatihan dan pendampingan manajemen keuangan dan laporan keuangan bumdes sempurna bangkalan: Bumdes sempurna bangkalan - Bambang Haryadi (Universitas Muhammadiyah Malang, 2023)
This community service aims to (1) provide an understanding of the importance of financial management and preparation of financial reports, (2) provide training and assistance in managing and preparing financial reports. This service was carried out at BUMDES Sempurna in Kamal village, Bangkalan Regency. Conducted for approximately 3 months, starting from October to December 2022. The methods used include: surveys, discussions and socialization on understanding financial management and financial reports, designing financial management and reports, making applications and conducting training on preparing financial reports based on MS Excel applications. The results of the training and mentoring showed that (1) before the mentoring, Bumdes Sempurna still did not know much about financial management and preparation, (2) After the mentoring, the BUMDES Sempurna management could understand the importance of financial management, there was already a separation of business unit managers, and already had a list of assets, (3) BUMDES was able to make and have financial reports based on MS Excel applications, including recording money in and out, profit and loss per business unit, profit and loss and consolidated balance sheet.